Design of a 20 Mbps OQPSK Modulator Based on Multiplexers - Prapto Nugroho (JURNAL INFOTEL, 2024)
This paper aims to delve into the design and implementation aspects of an OQPSK (Offset Quadrature Phase Shift Keying) modulator within the context of modem technology, underscoring its pivotal role in contemporary information technology infrastructure. The research primarily focuses on elucidating the theoretical foundations of OQPSK modulation, which represents an enhancement of QPSK modulation techniques. Central to the design is the utilization of a multiplexer to select one carrier signal out of four, which is subsequently modulated by data bits. Furthermore, the modulator employs two square wave signals phased 90 degrees apart, which are transformed into differential sinusoidal signals to constitute the carrier signal. Operating frequencies encompass a 5 MHz streaming data bits frequency and a 10 MHz clock frequency. Simulation results validate the efficacy of the OQPSK modulator by demonstrating its capability to generate modulated signals at a robust data transfer rate of 20 Mbps. This underscores the modulator's effectiveness in transmitting digital data over analog communication channels. In conclusion, the designed OQPSK modulator exemplifies its proficiency in efficiently modulating and demodulating signals, thereby bolstering connectivity and communication across diverse societal sectors. This research contributes significantly to the advancement of modem technology, which is indispensable for the expansion and maintenance of modern communication networks, ensuring robust connectivity in the digital age.